Levels of IL-23/IL-17 Axis in Plasma and Gingival Tissue of Periodontitis Patients According to the New Classification - Ruth Rodríguez-Montaño; Alondra del Carmen Ruiz-Gutiérrez; Vianeth María del Carmen Martínez-Rodríguez; Juan Ramón Gómez-Sandoval; Juan Manuel Guzmán-Flores; Julieta Sarai Becerra-Ruiz; Ana Lourdes Zamora-Perez; Celia Guerrero-Velázquez (Applied Sciences, 2022)
Background: Periodontitis (P) is a chronic inflammatory disease characterized by the destruction of periodontium support tissue generated by different immuno-inflammatory mechanisms, including the RANK/RANKL/OPG and the IL-23/IL-17 axis. Methods: The study was performed with healthy subjects (HS) and patients with periodontitis. Plasma samples were obtained from peripheral blood and the gingival tissue (GT) during periodontal surgery. The ELISA technique was used to evaluate the levels of IL-23, IL-17A, IL-23R, and IL-17RA. Results: In the plasma, a significant decrease in IL-17A was observed in patients with periodontitis than HS. In the GT, IL-23, IL-17A, and IL-17RA levels were increased in periodontitis patients; on the contrary, IL-23R levels were decreased in periodontitis patients when compared with HS. Finally, several positive correlations were found: soluble IL-17RA (sIL-17RA) levels in plasma between the percentage of radiographic bone loss (RBL%), and IL-23 with IL-17A in gingival tissue. Conclusions: The detection of the IL-23/IL-17A axis in gingival tissue and plasma provides us with more information on the behavior of this axis in a localized way in the periodontal microenvironment, in contrast to the systemic levels evaluated according to the new classification of periodontitis.